A Method Combining Mobile Transmissometer and Lidar for High Precision Measurement of Visibility - Meng Li; Guojin Wang (IEEE Photonics Journal, 2024)
High precision measurement of visibility has wide applications in the fields of civil aviation and maritime transportation. However, for a long time, the non-uniform of the atmosphere and optical contamination under low visibility have always been important issues affecting the measurement accuracy of visibility. This paper proposes a novel method that combines a mobile transmissometer with Lidar, which can not only accurately measure visibility in non-uniform atmospheric environments, but also effectively suppress environmental contamination by using the method of single end sampling. In this method, the mobile transmissometer is coupled with the Lidar at its baseline end, thereby effectively improving the Lidar measurement accuracy with the high-precision measurement results of the mobile transmissometer. The experimental and simulation results demonstrate that this method has better performances of anti noise and optical contamination suppression, compared to traditional Lidar and atmospheric transmissometer. It can achieve high-precision visibility measurement in a large range of non-uniform atmospheric environments, and also exhibits good robustness in low visibility environments.